Implementation of PSAK 109 in Zakat Management in North Kolaka Regency - Imran, Andi (Phinisi Applied Accounting Journal, 2024)
This research aims: To determine the accountability of zakat fund management at one of the Amil Zakat Agency in North Kolaka Regency based on PSAK 109. The respondents of this research are Amil Zakat officers consisting of four people representing each collection division, distribution division, utilization division, and division reporting and management reports for zakat funds in 2021. Data collection techniques were carried out using interviews and documentation. The data analysis uses qualitative descriptive, comparative analysis and the Coarse Conformity Index (IKK) formula. The results of this research indicate that zakat management at BAZNAS Kab. North Kolaka, includes the process of collecting, distributing, utilizing and reporting zakat in accordance with Law No. 23 of 2011. In terms of recognition, measurement and presentation, it is in accordance with PSAK 109 based on IKK calculations. However, in terms of disclosure, the application of PSAK 109 is not appropriate based on IKK calculations. Thus BAZNAS Kab. Kolaka is not yet fully compliant with PSAK 109.Penelitian ini bertujuan: Untuk mengetahui akuntabilitas pengelolaan dana zakat pada salah satu Badan Amil Zakat di Kabupaten Kolaka Utara berdasarkan PSAK 109. Responden penelitian ini adalah para petugas Amil Zakat terdiri dari empat orang yang mewakili setiap divisi pengumpulan, divisi pendistribusian, divisi pendayagunaan, dan divisi pelaporan dan laporan pengelolaan dana zakat tahun 2021. Teknik pengumpulan data dilakukan dengan wawancara dan dokumentasi. Adapun analisis data menggunakan deskriptif kualitatif, analisis komparatif dan rumus Indeks Kesesuaian Kasar (IKK). Hasil penelitian ini menunjukkan bahwa pengelolaan zakat pada BAZNAS Kab. Kolaka Utara, meliputi proses pengumpulan, pendistribusian, pendayagunaan dan pelaporan zakat sesuai dengan Undang-Undang No 23 Tahun 2011. Dalam segi pengakuan, pengukuran dan penyajian telah sesuai dengan PSAK 109 berdasarkan perhitungan IKK. Namun, dari sisi pengungkapan penerapan PSAK 109 tidak sesuai berdasarkan perhitungan IKK. Dengan demikian BAZNAS Kab. Kolaka belum sepenuhnya sesuai dengan PSAK 109.